Workload Perception and Job Satisfaction of Nurses at COVID-19 National Emergency Hospital Wisma Atlet Kemayoran, Jakarta, Indonesia - Setiyowati, Wahyu; Maha, Sukma Dewi Yusro; Prihantoro, Fajar Sigit; Sucipto, Sucipto; Wandasari, Noven Tri; Helmi, Mochamat; Endah, Sumarti; Effendy, Christanty (International Journal Labs, 2023)
The COVID-19 pandemic poses a major challenge to healthcare systems around the world. This is due to an imbalance between workload and the number of patients being treated. Nurses have an important role in determining the patient's recovery rate by providing intensive care management to patients, helping to fulfill the basic needs of patients, and collaborating with other health workers. This study aims to describe the workload perception and job satisfaction of nurses encountering the COVID-19 pandemic at the COVID-19 National Emergency Hospital Wisma Atlet Kemayoran (RSDC WAK), Jakarta, Indonesia. This study uses a descriptive study design. The sample of this study has inclusion criteria for nurses who work for the period January – May of 2022. This data collection uses instruments of nursing characteristics, nursing workload perception, and job satisfaction with Maslow’s Hierarchy of Needs. There were 105 samples of nurses chosen by convenience sampling. This study uses univariate (descriptive) statistical tests. The results show that the scale of nurse workload perception was often in the percentage (57.1%) with the most influential indicator being the psychological aspect which not being easy to deal with COVID-19 patients with different characteristics (37.1%) and the physical aspect because of the large amount of work that must be done for patient safety (36.2%). The result of job satisfaction was very satisfactory (57.1%) with the most influential indicator being the attitude of a very good colleague (49.5%) and cooperation between nurses (46.7%). The workload perception and job satisfaction information can be a reference for implementing nursing management strategies that pay attention to health, motivation, and work productivity to maintain the quality of nursing care during a pandemic.